![\displaystyle \tt 1). \ \ \frac{18}{x}-\frac{46}{x-5}=1\\\\{} \ \ \ \ \ \ 18\cdot(x-5)-46x=x^{2}-5x\\\\{} \ \ \ \ \ \ x^{2}+23x+90=0 \ \ \ \ \ \ \ D=b^{2}-4ac=169=13^{2}\\\\{} \ \ \ \ \ \ x_{1,2}=\frac{-bб\sqrt{D}}{2a}\\\\{} \ \ \ \ \ \ x_{1}=-5\\\\{} \ \ \ \ \ \ x_{2}=-18 \displaystyle \tt 1). \ \ \frac{18}{x}-\frac{46}{x-5}=1\\\\{} \ \ \ \ \ \ 18\cdot(x-5)-46x=x^{2}-5x\\\\{} \ \ \ \ \ \ x^{2}+23x+90=0 \ \ \ \ \ \ \ D=b^{2}-4ac=169=13^{2}\\\\{} \ \ \ \ \ \ x_{1,2}=\frac{-bб\sqrt{D}}{2a}\\\\{} \ \ \ \ \ \ x_{1}=-5\\\\{} \ \ \ \ \ \ x_{2}=-18](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Ctt%201%29.%20%5C%20%5C%20%5Cfrac%7B18%7D%7Bx%7D-%5Cfrac%7B46%7D%7Bx-5%7D%3D1%5C%5C%5C%5C%7B%7D%20%5C%20%5C%20%5C%20%5C%20%5C%20%5C%2018%5Ccdot%28x-5%29-46x%3Dx%5E%7B2%7D-5x%5C%5C%5C%5C%7B%7D%20%5C%20%5C%20%5C%20%5C%20%5C%20%5C%20x%5E%7B2%7D%2B23x%2B90%3D0%20%5C%20%5C%20%5C%20%5C%20%5C%20%5C%20%5C%20D%3Db%5E%7B2%7D-4ac%3D169%3D13%5E%7B2%7D%5C%5C%5C%5C%7B%7D%20%5C%20%5C%20%5C%20%5C%20%5C%20%5C%20x_%7B1%2C2%7D%3D%5Cfrac%7B-b%D0%B1%5Csqrt%7BD%7D%7D%7B2a%7D%5C%5C%5C%5C%7B%7D%20%5C%20%5C%20%5C%20%5C%20%5C%20%5C%20x_%7B1%7D%3D-5%5C%5C%5C%5C%7B%7D%20%5C%20%5C%20%5C%20%5C%20%5C%20%5C%20x_%7B2%7D%3D-18)
Ответ: {-5; -18}
\ \ \left \{ {{y=7x-5 \ \ \ \ \ } \atop {x(7x-5)=18}} \right.\\\\\\{}\ \ \ \ \ \ \ 7x^{2}-5x-18=0 \ \ \ \ \ \ \ D=b^{2}-4ac=25+504=529=23^{2}\\\\{} \ \ \ \ \ \ \ x_{1,2}=\frac{-bб\sqrt{D}}{2a}\\\\{} \ \ \ \ \ \ \ x_{1}=2 \ \ \ \ \ \ \ \ \ \ \ \ y_{1}=9\\\\{} \ \ \ \ \ \ \ x_{2}=-1\frac{2}{7} \ \ \ \ \ \ \ y_{2}=-14" alt="\displaystyle \tt 2). \ \ \left \{ {{7x-y=5} \atop {xy=18 \ \ \ }} \right. \ \ <=> \ \ \left \{ {{y=7x-5 \ \ \ \ \ } \atop {x(7x-5)=18}} \right.\\\\\\{}\ \ \ \ \ \ \ 7x^{2}-5x-18=0 \ \ \ \ \ \ \ D=b^{2}-4ac=25+504=529=23^{2}\\\\{} \ \ \ \ \ \ \ x_{1,2}=\frac{-bб\sqrt{D}}{2a}\\\\{} \ \ \ \ \ \ \ x_{1}=2 \ \ \ \ \ \ \ \ \ \ \ \ y_{1}=9\\\\{} \ \ \ \ \ \ \ x_{2}=-1\frac{2}{7} \ \ \ \ \ \ \ y_{2}=-14" align="absmiddle" class="latex-formula">
Ответ: {2; 9}, {-1 2/7; -14}